Development of Sports Massage Based on BOD Sports Massage Application - Permana Putra, Muhamad Difa; Aulia, Dany; Izzuddin, Deden Akbar; Wijaya, Habibi Hadi (UNIVERSITAS NEGERI MAKASSAR, 2025)
This study aims to create an application that can be used to order massage services based on Android called BOD Sports Massage. This type of research uses Research and Development (R&D). The design of this study uses the simplified Borg And Gall design with several stages of research into 1. data collection 2. product design 3. product development 4. validation and revision 5. field trials 6. Product improvement and maintenance. The subjects in this study were members of the Persaudaraan Setia Hati Terate Organization totaling 60 people. The sample was selected using a random sampling technique. The test instrument used in this study used a Likert scale. Based on the trial data of the BOD Sports Massage Application, it shows that the assessment of the feasibility of the contents of this application is 80.30% which is included in the good/feasible category, in terms of appearance 90% and from the usage value of 90.1%, the total of all feasibility assessments of the BOD Sport Massage Application is 87.6% and is included in the Good/Feasible category so that it can be concluded that the product can be used to order massage services for athletes and the general public.